FOOTBALL GAME BASIC ABILITY - Budi Artina (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Sport is a highly developed aspect of human life. Exercise is one of the human needs that is carried out so that the body stays healthy and fit. The game of football is more dominant by using the feet played by people from various social circles. In Passing and control the Barona FC players made a mistake in doing it not as desired, then in dribbling the players had difficulty dribbling the ball when facing an opponent, when shooting towards goal, the ball was always far from the target of the opponent's goal, and heading errors often occurred on the forehead which resulted in the ball going off the mark and the heading being done imperfectly. This is due to the lack of basic technical skills of the players, many things are found in a match, the players have not mastered the basic techniques in a soccer team, because in soccer games basic techniques are the main capital for playing soccer. The results of the study found that SSB Barona FC was still not maximal in increasing achievement. This is caused by the basic techniques of the athletes who have not been maximized.